2016
DOI: 10.1016/j.canlet.2016.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of invasion and metastasis in aggressive salivary cancer cells through targeted inhibition of ID1 gene expression

Abstract: Salivary gland cancer (SGC) represents the most common malignancy in the head and neck region, and often metastasizes to the lungs. The helix–loop–helix ID1 protein has been shown to control metastatic progression in many types of cancers. Using two different approaches to target the expression of ID1 (genetic knockdown and progesterone receptor introduction combined with progesterone treatment), we previously determined that the aggressiveness of salivary gland tumor ACCM cells in culture was suppressed. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…ID protein inhibition by a peptide aptamer induces cell cycle arrest and apoptosis in ovarian cancer cells ( Mern et al, 2010a ). Suppression of invasion and metastasis in aggressive salivary and breast cancer cells is targeted through inhibition of ID1 expression ( Fong et al, 2003 ; Murase et al, 2016 ). Inactivation of ID1 genes induces sensitivity of prostate cancer cells to chemotherapeutic drugs ( Wong et al, 2008 ).…”
Section: Current Anticancer Therapeutic Approaches In Agreement With mentioning
confidence: 99%
“…ID protein inhibition by a peptide aptamer induces cell cycle arrest and apoptosis in ovarian cancer cells ( Mern et al, 2010a ). Suppression of invasion and metastasis in aggressive salivary and breast cancer cells is targeted through inhibition of ID1 expression ( Fong et al, 2003 ; Murase et al, 2016 ). Inactivation of ID1 genes induces sensitivity of prostate cancer cells to chemotherapeutic drugs ( Wong et al, 2008 ).…”
Section: Current Anticancer Therapeutic Approaches In Agreement With mentioning
confidence: 99%
“…Down-regulation of ID1 expression leads to a significant reduction in lung metastasis in mice injected intravenously with ACCM cells. 22…”
Section: Etiology and Pathology Of Salivary Tumorsmentioning
confidence: 99%
“…In short, phytocannabinoids (THC, CBD), ECs and EC analogue (AEA, 2-AG, Met-F-AEA), EC-like substances (OEA, PEA) and EC degradation inhibitors (AA-5HT, URB597, JZL184) showed an inhibitory effect on metastatic infiltration of the lung with previously injected lung carcinoma cells [ 32 , 36 , 90 , 93 , 112 , 113 ]. In addition, inhibitory effects of cannabinoids on breast cancer [ 101 , 102 , 114 ], salivary gland cancer [ 100 ] and melanoma cell metastasis [ 44 ] have been described. Finally, further work showed that JZL184 impairs bone metastasis of osteotropic prostate and breast cancer cells in mice and inhibits metastasis of osteosarcoma cells [ 115 ] and that knockdown of MAGL is associated with reduced lymph node metastasis in MAGL-overexpressing nasopharygeal carcinoma cells [ 116 ].…”
Section: Tumour Cell Invasion and Metastasismentioning
confidence: 99%